Dylematy menedżera w rozwijaniu działalności gospodarczej na rynkach międzynarodowyc - Kuźniak, Krzysztof Kazimierz (Managerial Controversies in Developing Economic Activities on Global Markets, 2008)
The paper presents the problem of communication barriers that may occur during company economic expansion on global markets. Apart from natural dangers resulting from language barriers, the process may create other problems due to cultural differences, both on professional and personal level. The paper addresses such issues as universal language of business, cultural differences in negotiation, universal work model and perspectives for Polish companies after Poland's accession to EU structures.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 17, s. 42-48